Isolation, Chromosomal Localization, and Differential Expression of Mitochondrial Manganese Superoxide Dismutase and Chloroplastic Copper/Zinc Superoxide Dismutase Genes in Wheat - Wu, Guohai (American Society of Plant Physiologists, 1999)
Superoxide dismutase (SOD) gene expression was investigated to elucidate its role in drought and freezing tolerance in spring and winter wheat (Triticum aestivum). cDNAs encoding chloroplastic Cu/ZnSODs and mitochondrial MnSODs were isolated from wheat. MnSOD and Cu/ZnSOD genes were mapped to the long arms of the homologous group-2 and -7 chromosomes, respectively. Northern blots indicated that MnSOD genes were drought inducible and decreased after rehydration. In contrast, Cu/ZnSOD mRNA was not drought inducible but increased after rehydration. In both spring and winter wheat seedlings exposed to 2°C, MnSOD transcripts attained maximum levels between 7 and 49 d. Transcripts of Cu/ZnSOD mRNA were detected sooner in winter than in spring wheat; however, they disappeared after 21 d of acclimation. Transcripts of both classes of SOD genes increased during natural acclimation in both spring and winter types. Exposure of fully hardened plants to three nonlethal freeze-thaw cycles resulted in Cu/Zn mRNA accumulation; however, MnSOD mRNA levels declined in spring wheat but remained unchanged in winter wheat. The results of the dehydration and freeze-thaw-cycle experiments suggest that winter wheat has evolved a more effective stress-repair mechanism than spring wheat.